Asian snake farms: conservation curse or sustainable enterprise?. Issue 3 (1st July 2016) - Aust, Patrick W.; Van Tri, Ngo; Natusch, Daniel J.D.; Alexander, Graham J.
Abstract: Snake farming in Asia has increased over the past decade, and conservationists have expressed concerns that farms may foster overexploitation of wild populations and create legal conduits for illegally harvested wild individuals. We conducted face-to-face interviews with snake farmers in Viet Nam and China, with the aim of describing the basic models under which snakes are farmed for meat. We synthesized this information to assess the feasibility of farming snakes for human consumption, drawing conclusions about the impact of this industry on the conservation of wild snake populations. The most commonly farmed snakes include the monocled cobra Naja kaouthia, the Chinese cobra Naja atra, the oriental rat snake Ptyas mucosus and the king cobra Ophiophagus hannah . These species have life histories that are compatible with the demands of intensive livestock production, including early maturity, rapid growth rates, high reproductive output, efficient food assimilation rates and undemanding space requirements. Snake farmers appear to be capitalizing on the unique energy-efficiency of snakes to produce meat for human consumption. We conclude that the ease and profitability of farming snakes in China and Viet Nam make farming a viable substitute for harvesting wild snakes, with apparently minimal threat to wild populations. Snake farming offers a range of novel agricultural opportunities and has the potential to play a pivotal role in sustainable development.